Bridging Lecturers’ Well-being: Analyzing Sleep Patterns, Stress, and Health Outcomes through Participatory Approaches - Kalaga V N S, Anjanee Gayatri; Murari, Monika Sai (Help: Journal of Community Service, 2025)
The relationship between lifestyle choices and psychological well-being has gained increasing attention in workplace wellness research, particularly within educational institutions. College faculty members often face significant challenges due to heavy workloads, academic pressures, and administrative responsibilities, which may impact their mental health. This study aims to examine the correlation between lifestyle habits—such as work-life balance, diet, sleep patterns, and physical activity—and the psychological well-being of college faculty members. This research adopts a cross-sectional survey approach, collecting primary data through questionnaires from lecturers at St. Ann’s College for Women, Mehdipatnam, Hyderabad. Participants were selected using a random sampling method. The survey included demographic information and questions related to healthy lifestyle practices that may influence psychological well-being. Data analysis was conducted using MS Excel, SPSS, and R programming, employing correlation, regression analysis, and Analysis of Variance (ANOVA) to determine the significance of associations between variables. The findings reveal key patterns in lifestyle habits that correlate with faculty members' psychological well-being. Statistical analyses indicate that certain factors, such as balanced sleep patterns and regular physical activity, have a positive association with mental health, while work-life imbalance and poor dietary choices negatively impact psychological well-being. This study contributes to the growing body of research on occupational health by offering evidence-based recommendations for institutional policy improvements. It suggests implementing faculty wellness programs and fostering a supportive work environment to enhance both individual well-being and institutional productivity.